2012
DOI: 10.1128/jb.06567-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Flavonoid-Responsive Regulator FrrA and Its Binding Sites

Abstract: Previous microarray analyses revealed that in Bradyrhizobium japonicum, about 100 genes are induced by genistein, an isoflavonoid secreted by soybean. This includes the three genes freC, freA, and freB (systematic designations bll4319, bll4320, and bll4321), which are likely to form a genistein-, daidzein-, and coumestrol-inducible operon and to encode a multidrug efflux system. Upstream of freCAB and in the opposite orientation, FrrA (systematic designation Blr4322), which has similarity to TetRtype regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
(55 reference statements)
3
11
0
Order By: Relevance
“…4). This suggests MfsR-His6 to form homodimers in solution, which is in agreement with several observations that TetR family members occur as homodimers (31,32). Even larger protein bands were seen in cross-linked preparations (e.g., 95 kDa) ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…4). This suggests MfsR-His6 to form homodimers in solution, which is in agreement with several observations that TetR family members occur as homodimers (31,32). Even larger protein bands were seen in cross-linked preparations (e.g., 95 kDa) ( Fig.…”
Section: Resultssupporting
confidence: 77%
“…These two regulators were not arranged in parallel and are both under the Gac/Rsm system; orf1 was upstream of orf12 in the biosynthesis of 7-HT in P. donghuensis HYS. Members of the TetR/AcrR family mainly act as repressors by forming homodimers and binding to the operator of target DNAs (28,29). In this study, the repression of orf9 expression via the overexpression of Orf12 may also occur through the formation of dimers; however, this speculation requires further study.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies have shown that the “two-component system” regulates the specific gene expression of rhizobia by recognizing additional plant and environmental signals, which affects rhizobial ability to colonize roots. It also affects the competitive performance of rhizobia 19 , 47 , 48 . This study showed that a total of 19 genes were related to the “two-component system”, which was found to be significantly enriched in the KEGG analysis (Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%